1998
DOI: 10.2527/1998.7671970x
|View full text |Cite
|
Sign up to set email alerts
|

Complementary responses between feather meal and poultry by-product meal with or without ruminally protected methionine and lysine in growing calves.

Abstract: We evaluated feather meal (FTH) and poultry by-product meal (PBM) as complementary protein sources for growing calves. In a replicated 84-d growth trial, individually fed steer calves (n = 120; 252 +/- 24 kg) were supplemented with urea or with graded levels of soybean meal (SBM), FTH, PBM, or 2/3 FTH:1/3 PBM (CP basis). Protein efficiency, calculated as gain above the urea control vs natural protein intake using the slope-ratio technique, was greater for FTH than for SBM, PBM, and 2/3 FTH:1/3 PBM (P < .10). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
(34 reference statements)
1
10
1
Order By: Relevance
“…Despite the fact that the spent hen meal used in this study contained soybean meal, the ruminal undegraded protein value for spent hen–soybean meal blend was higher than the value reported for poultry by‐product by Klemesrud et al 27 and was similar to that reported by Bohnert et al 8 These results suggest that spent hen meal has a higher ruminal undegraded protein value than poultry by‐product. This is presumably due to the presence in the spent hen of materials such as feathers and bones which are characterised by high ruminal undegraded protein values 8.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Despite the fact that the spent hen meal used in this study contained soybean meal, the ruminal undegraded protein value for spent hen–soybean meal blend was higher than the value reported for poultry by‐product by Klemesrud et al 27 and was similar to that reported by Bohnert et al 8 These results suggest that spent hen meal has a higher ruminal undegraded protein value than poultry by‐product. This is presumably due to the presence in the spent hen of materials such as feathers and bones which are characterised by high ruminal undegraded protein values 8.…”
Section: Resultssupporting
confidence: 75%
“…However, ruminal degradability of poultry by‐product meal has been determined by several researchers 8. 27 Bohnert et al 8 reported that poultry by‐product meal has a higher in situ soluble crude protein fraction than soybean meal. However, owing to the higher rate of degradation, soybean meal is more degradable in the rumen than poultry by‐product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that feather protein has been showed to be an excellent source of metabolizable protein (10), and that microbial keratinases enhance the digestibility of feather keratin (12,20), these keratinolytic strains could be used to produce animal feed protein. In addition, the selected isolates were able to grow and display keratinolytic activity in diverse keratin wastes.…”
Section: Discussionmentioning
confidence: 99%
“…1983). Feather protein has been considered as an excellent source of metabolizable protein (Klemersrud et al . 1998) and bacterial feather lysate has similar nutritional features to soybean meal (Williams et al .…”
Section: Discussionmentioning
confidence: 99%